Locus of control, self-concept and emotional intelligence as correlates of academic achievement among adolescents in senior secondary schools in Oyo state (2006)
The study investigated locus of control, self-concept and emotional intelligence as predictors of academic achievement among senior secondary students in Oyo state. Participants consisted of 600 students (370 boys and 230 girls) from four senior secondary schools in four educational zones of Oyo state. The oarticipants who were SS2 students with age ranging between 14 and 20 years with a calculated mean age of 16.2 years and a standard deviation of 3.6 were randomly selected. The students responded to valid and reliable instruments namely: locus of control scale, self-concept and emotional intelligence scale and general aptitude test. Data analysis involved multile regression, to examin the predictive effect of locus of control, self concept and emotional intelligence on the students'academic achievement. Results showed that the variables when taken jointly and relatively, predicted and the need for guidance services in Nigerian secondary schools was also stressed.